Mobilisation plans of a Separate Border Guard Corps of the Russian Empire and their implementation at the beginning of the World War I (1904–1914) - Lukashevich, Andrei M. (Journal of the Belarusian State University. History, 2024)
The article reveals the preparation process and content of mobilisation plans of the Separate Border Guard Corps of the Russian Empire on the eve of the World War I. The place and role of the Corps in the armed forces is determined. The mechanism for preparing mobilisation plans of the Separate Border Guard Corps is analysed and its stages are highlighted. The content of the mobilisation plans of the 2nd (Vilna) and 3rd (Warsaw) border districts is revealed, and their evolution during the 1910s is traced. It is noted that the initial plans of the Separate Border Guard Corps provided for predominantly passive (defensive) actions (withdrawal from the border deep into its territory with the simultaneous destruction of bridges, crossings, railways and other objects). Introduced 1911–1913 changes in these plans were due to the need to take into account the military-strategic ideas of the allies (France) and opponents (Germany and Austria-Hungary). It is concluded that the mobilisation plans of the Separate Border Guard Corps, adjusted by 1914, provided for, with the declaration of war, active actions of border guard units in the adjacent territory (conducting reconnaissance, disrupting the mobilisation of the enemy, carrying out sabotage, etc.). At the same time, the actual course of events showed that the actions of the border guards in the first weeks of the World War were of a hybrid nature and, depending on the theater of military operations, contained elements of the mobilisation planning of the 1900s and 1910s.
Keywords: Russian Empire; Separate Border Guard Corps of the Russian Empire; World War I; German Empire; AustroHungarian Empire; mobilisation plans; border brigades